2006
DOI: 10.1016/j.taap.2005.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of maternal atrazine exposure on male Balb/c mice

Abstract: Atrazine is a widely used herbicide applied to corn, sugar and other crops as a broad leaf weed inhibitor. Using the Balb/c mouse model, we have determined that prenatal/lactational exposure to atrazine alters adult immune function. Pregnant Balb/c dams were exposed subcutaneously for 21 days via time release pellets to 700 microg per day of atrazine beginning between days 10 and 12 of pregnancy. Prenatal/Lactational exposure caused no overt physical malformations in the offspring and had no effect on the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
5
48
0
Order By: Relevance
“…Rowe et al used timerelease pellets to subcutaneously expose pregnant Balb/c dams to 700 μg/day of ATR for 21 days from day 10 and day 12 of pregnancy. At 3 months of age, male, but not female, mouse pups had increases in T cell proliferation, cytolytic activity, and the number of IgM-secreting B cells in the spleen, but there were no marked changes in the body weight, organ-to-body weight ratio of the spleen, and the numbers of CD8+ T cells, CD4+ T cells, and B220+ B cells in the spleen (25).…”
mentioning
confidence: 87%
“…Rowe et al used timerelease pellets to subcutaneously expose pregnant Balb/c dams to 700 μg/day of ATR for 21 days from day 10 and day 12 of pregnancy. At 3 months of age, male, but not female, mouse pups had increases in T cell proliferation, cytolytic activity, and the number of IgM-secreting B cells in the spleen, but there were no marked changes in the body weight, organ-to-body weight ratio of the spleen, and the numbers of CD8+ T cells, CD4+ T cells, and B220+ B cells in the spleen (25).…”
mentioning
confidence: 87%
“…Besides effects on the nervous system, ATR exposure can adversely affect the immune system, with thymus being affected more than the spleen shortly after exposure (National Toxicology Program, 1994;Pruett et al, 2003;Filipov et al, 2005;Karrow et al, 2005;Rowe et al, 2006). However, thymus cellularity seems to recover from the effects of ATR, whereas splenic cellularity is reduced up to 7 weeks after exposure termination (Filipov et al, 2005).…”
Section: Ross Et Almentioning
confidence: 99%
“…Although data on health effects of ATR in humans are not complete, an increasing number of animal studies report that ATR exposure causes reproductive, developmental, and immunological alterations in laboratory rodents (Cooper et al, 1996Narotsky et al, 2001;Pruett et al, 2003;Filipov et al, 2005;Giusi et al, 2006;Rowe et al, 2006). The brain is another potential target organ for ATR as several in vitro and in vivo studies have suggested that excessive exposure to ATR may be neurotoxic (Das et al, 2000(Das et al, , 2001Rodriguez et al, 2005;Giusi et al, 2006;Coban and Filipov, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Adverse effects of atrazine also affect human health. 2 In fact, atrazine is an endocrine disruptor and corelates with breast and reproductive disorders in mammalians. 3 Atrazine at present is widely used in USA and, although it has been withdrawn from the market in several European countries, analogous molecules (as terbuthylazine differing only by side chain methyl groups) are currently used.…”
Section: Introductionmentioning
confidence: 99%